How am I feeling? (London Dorling kindersly, 2020)
This board book helps young children understand their emotions and how their feelings can influence their actions. It is often difficult for children, and adults, to articulate their emotions and to understand why they act the way they do. This colourful illustrated board book encourages pre-schoolers to understand what is happening in their body when they feel happy or sad, and how strong feelings can shape their actions
1 23
Keywords: Board books; Emotions; picture books